Researchers’ reflections on values, mechanisms, and dynamics of knowledge and information sharing in international academic projects - Rak, Dorota; Khosrowjerdi, Mahmood; Muthelo, Livhuwani; Mukherjee, Bhaskar (Information Research an international electronic journal, 2025)
Introduction. Knowledge/information sharing is among the vital necessities of effective scholarly collaborations. This study investigates the role of knowledge/information sharing among project members in international academic projects through the lens of Structuration Theory. Method. The study is based on semi-structured interviews with 28 academicians and researchers from India, Norway, Poland, and South Africa, who have been involved in international academic projects. Analysis. The transcriptions were imported into F4Analyse software (version 3.4.5) and were coded. Results. The study reveals three main themes: 1) the significance and value of sharing, 2) mechanisms and platforms for effective communication and sharing, and 3) interpersonal dynamics and challenges in sharing. Each theme highlights critical aspects of the dynamics in international academic collaborations. Conclusions. The findings underscore the complexities and challenges in these collaborations, such as power dynamics, the potential risks of sharing, and the possibility for exploitation. The study concludes that the process of sharing transcends mere dissemination of information, being deeply rooted in mutual respect, acknowledgment of contributions, and openness. This study contributes to a deeper understanding of the dynamics of information sharing in international academic collaborations.